Inhibition of the AnxA1/FPR1 autocrine axis reduces MDA-MB-231 breast cancer cell growth and aggressiveness in vitro and in vivo - Vecchi, Lara; Alves Pereira Zóia, Mariana; Goss Santos, Tiago; de Oliveira Beserra, Adriano; Colaço Ramos, Cristiano Manuel; França Matias Colombo, Bruna; Paiva Maia, Yara Cristina; Piana de Andrade, Victor; Teixeira Soares Mota, Sara; Gonçalves de Araújo, Thaise; Van Petten de Vasconcelos Azevedo, Fernanda; Soares, Fernando Augusto; et al. (Elsevier, 2018)
Breast Cancer (BC) is a highly heterogeneous disease whose most aggressive behavior is displayed by triple-negative breast cancer (TNBC), which lacks an efficient targeted therapy. Despite its controversial role, one of the proteins that having been linked with BC is Annexin A1 (AnxA1), which is a Ca+2 binding protein that acts modulating the immune system, cell membrane organization and vesicular trafficking. In this work we analyzed tissue microarrays of BC samples and observed a higher expression of AnxA1 in TNBCs and in lymph node metastasis. We also observed a positive correlation in primary tumors between expression levels of AnxA1 and its receptor, FPR1. Despite displaying a lesser strength, this correlation also exists in BC lymph node metastasis. In agreement, we have found that AnxA1 was highly expressed and secreted in the TNBC cell line MDA-MB-231 that also expressed high levels of FPR1. Furthermore, we demonstrated, by using the specific FPR1 inhibitor Cyclosporin H (CsH) and the immunosuppressive drug Cyclosporin A (CsA), the existence of an autocrine signaling of AnxA1 through the FPR1. Such signaling, elicited by AnxA1 upon its secretion, increased the aggressiveness and survival of MDA-MB-231 cells. In this manner, we demonstrated that CsA works very efficiently as an FPR1 inhibitor. Finally, by using CsA, we demonstrated that FPR1 inhibition decreased MDA-MB-231 tumor growth and metastasis formation in nude mice. These results indicate that FPR1 inhibition could be a potential intervention strategy to manage TNBCs displaying the characteristics of MDA-MB-231 cells. FPR1 inhibition can be efficiently achieved by CsA.
Keywords: Annexin A1; Autocrine signaling; Cyclosporin A; Cyclosporin H; FPR1; Triple-negative breast cancer